Year 2000 : compliance criteria - Malta Information Technology & Training Services L (MITTS Blata I-BajdaMT, 1998)
Presents MITTS criteria for 'year 2000 compliance'. Provides a background to the problem and defines the scope of the Year 2000 primarily from a software development perspective.